Effect of Oral Allopurinol in Elevated Liver Enzyme Reduction in Pediatric Acute Lymphoblastic Leukemia During Maintenance Therapy - Molaei Tavana, Parastoo; Momtazmanesh, Nader; Shamshiri, Ahmadreza; Jali, Zohre (Novelty in Biomedicine, 2026)
Background: Acute lymphoid leukemia (ALL) represents a prevalent form of cancer in pediatric populations. Mercaptopurine is one of the proposed treatments for these patients. This treatment may cause multiple side effects, including liver-related effects. Allopurinol has been proposed as a means to mitigate hepatotoxicity, but the previous studies in this regard remain scarce. This study aimed to investigate the effect of allopurinol on preventing increases in liver enzymes in children with ALL during the maintenance phase of drug treatment. Materials and Methods: This is a double-blind clinical trial conducted on children with ALL receiving maintenance treatment with mercaptopurine during the maintenance phase of the disease. Patients were categorized into two groups. The initial cohort of 25 individuals was administered mercaptopurine tablets in combination with allopurinol tablets. The second group, comprising an equivalent number of patients, was administered mercaptopurine tablets and a placebo. Laboratory studies were evaluated. The patients’ data were analyzed at the 0.05 significance level. Results: The mean age in group A was 7.64 ± 3.78 years, while in group B it was 6.92 ± 3.19 years. In group A, the proportion of boys was 44%, whereas in group B, it was 72%. In both groups, the majority of patients tolerated less than 75 mg of mercaptopurine per body surface area, whereas, for methotrexate, most patients tolerated less than 20 mg per body surface area. Allopurinol significantly reduced mercaptopurine-induced hepatotoxicity in pediatric patients with ALL (P-value < 0.05). Allopurinol significantly reduced alanine transaminase (ALT) and aspartate aminotransferase (AST) levels compared to placebo (P-value<0.05). The intra-group analysis indicated that allopurinol significantly reduced enzyme levels over time (all P-values < 0.05). Conclusion: Allopurinol reduces hepatotoxicity in ALL patients receiving mercaptopurine.